Weighted absolute degree of grey incidence with TOPSIS and its application. Issue 2 (1st August 2016) - Li, Qian
Abstract : Purpose: – The purpose of this paper is to evaluate and rank the influence of internet public opinion of China's Government work in 2015 by weighted absolute degree of grey incidence with TOPSIS. Design/methodology/approach: – This disaggregation method includes four main steps, determine the vector of weights for the factors by analytic hierarchy process, calculate the matrix of consistent effect measure, determine the weighted absolute degree of grey incidence with TOPSIS, rank and evaluate the events. Findings: – We get the ranking of internet public opinion of China's Government work in 2015 by weighted absolute degree of grey incidence with TOPSIS. The result can be used for evaluating and ranking the influence of internet public opinion in China. The positive weighted absolute degree of grey incidence, the negative weighted absolute degree of grey incidence and the weighted absolute degree of grey incidence with TOPSIS have the same ranking results. The same ranking results show that the method of weighted absolute degree of grey incidence with TOPSIS has good consistency. Practical implications: – The weighted absolute degree of grey incidence with TOPSIS can be easily used for other evaluation. Originality/value: – The weighted absolute degree of grey incidence with TOPSIS is proposed and first used for evaluating and ranking the influence of internet public opinion of China's Government work.